Komodifikasi Disabilitas dalam Iklan Tommy Hilfiger, Gucci, dan Smarteyes Denmark - Akhlakulkarimah, Dinda; Adipurwawidjana, Ari J.; Katrine Rask Andersen (The Journal of Society and Media, 2025)
This study examines the commodification of individuals with disabilities in advertisements by prominent fashion brands such as Tommy Hilfiger, Gucci, and Smarteyes Denmark. The research is grounded in the growing narrative of inclusivity within the fashion industry, which, on the one hand, opens up representational space, but on the other often masks visual exploitation. Using a semiotic approach, this study analyses how disabled bodies are constructed within the visual and discursive frameworks of fashion advertising. Findings reveal that such representations frequently combine disability with a superficial aesthetic of diversity, wherein disabled bodies are depicted not as complex subjects, but as empathetic objects commodified for brand image purposes. The study highlights the need for a critical reading of the interrelation between disability, gender, and power dynamics in the contemporary commercial media landscape.